Poultry health constraints in smallholder village poultry systems in Northern Ghana and Central Tanzania - Ouma, Emily A.; Kankya, C.; Dione, Michel M.; Kelly, T.; Enahoro, Dolapo K.; Chiwanga, G.; Abukari, Y.; Msoffe, P.; Kayang, B.B.; Zhou, H. (Frontiers Media, 2023)
Introduction: Smallholder poultry production is a major contributor to food security and rural livelihoods in low-and middle-income countries. However, infectious diseases limit improvements to smallholder poultry production and performance of the sector in general. Infectious diseases of poultry, especially viral diseases, have major impacts on the health and productivity of flocks and account for significant morbidities and mortalities of birds each year.